Estimation of medical radionuclide yields in photonuclear production - Dikiy, N.P.; Dovbnya, A.N.; Nikiforov, V.I.; Uvarov, V.L. (Вопросы атомной науки и техники, 2006)
The present paper reports the results from computer simulation of the processes of radionuclide production, namely, Sc-47, Co-57, Cu-67, Mo-99, Pd-103, In-111, W-181 and Ir-192. Consideration was given to a simplified 2D-geometry version of the target device that includes a 4 mm thick tungsten bremsstrahlung converter and a cylindrical target of natural isotopic composition that follows the converter. Radionuclide yields (gross and specific activities) were obtained as functions of electron energies (30 to 100 MeV) at an accelerator current of 200 μA.